EMPLOYEE COMPETENCY IN USING THE SRIKANDI APPLICATION IN SALAM BABARIS DISTRICT TAPIN REGENCY - Enggok, Murakhman Sayuti; Normajatun, Normajatun; Hairansyah, Hairansyah; Maulida Rahmah, (International Journal of Social Science, 2025)
The purpose of this study was to determine employee competency and obstacles in using the Srikandi Application in Salam Babaris District, Tapin Regency. The research method used a qualitative approach with a descriptive research type. Data were collected through observation, documentation and interviews to four informants consisting of the Sub-district Head, Sub-district Secretary, Head of General and Personnel Sub-division and Operator Staff. Data analysis was carried out qualitatively. The results of the study indicate that employee competency in using the Srikandi Application is: most employees have understood the basic functions of the application, but have not fully mastered the advanced features, there is a gap in technical ability between employees who are accustomed to using computers and those who are not, some employees have high self-confidence in facing digitalization while others are still lacking, responsible personality in accelerating adaptation, and there are differences in employee motives in using digitalization and the role of the application in supporting work success. The obstacles faced includelow technical skills, unstable motives, minimal ongoing training and inadequate facilities and infrastructure